Students' Learning Outcomes in Science and Social Studies (IPAS) through the Picture and Picture Cooperative Learning Model - Wasti Yakobus; Samuel P. Ritiauw; Sefanya Sairiltiata (ETDC: Indonesian Journal of Research and Educational Review, 2026)
This study aimed to improve the Science and Social Studies (Ilmu Pengetahuan Alam dan Sosial, IPAS) learning outcomes of Grade IV students at Elementary School Syota, Pulau Moa District, Southwest Maluku Regency, Indonesia—a school situated in a remote, outermost, and underdeveloped (Terdepan, Terluar, dan Tertinggal, 3T) archipelagic region—through the implementation of the Picture and Picture cooperative learning model. A Classroom Action Research (CAR) design was employed, comprising two cycles conducted from August to September of the 2024/2025 academic year and involving 12 Grade IV students (8 male, 4 female) as research subjects. Data were collected through written achievement tests, structured classroom observation, and documentation and were analyzed using quantitative descriptive statistics benchmarked against the school's Learning Objective Achievement Criteria (Kriteria Ketercapaian Tujuan Pembelajaran, KKTP). The findings indicated classical learning mastery increased consistently across the three assessment points, from 45.45% at the pre-test to 63.63% at the end of Cycle I and 100% at the end of Cycle II, accompanied by a rise in the class mean score from 72.72 to 85.00. Reflective refinements introduced between cycles — including strengthened scaffolding, improved visual instructional materials, and more consolidated formative feedback — were instrumental in the substantial gains observed in Cycle II. The findings offer a low-cost, technology-independent instructional alternative that teachers in resource-constrained island schools can readily adopt to strengthen conceptual understanding and active participation in IPAS instruction.